Pengaruh Arang Sekam dan Konsentrasi Eco-Enzim Buah terhadap Pertumbuhan Bibit Kelapa Sawit di Pre-Nursery - Darmawanto, Doni; Parwati, Wiwin Dyah Ully; Soebroto, Setyastuti Purwanti (Program Studi Agroteknologi INSTIPER, 2024)
This research aims to assess the impact of rice husk charcoal and fruit eco-enzyme concentrations on the growth of oil palm seedlings during the pre-nursery stage. Conducted in Wedomartani, Ngemplak, Sleman, Yogyakarta, from May to August 2024, the study employed a factorial experiment using a Completely Randomized Design (CRD) with two factors. The first variable was rice husk charcoal with four treatment levels: no charcoal (control), ratio of husk charcoal and topsoil 1:4, ratio of husk charcoal and topsoil 1:2, and ratio of husk charcoal and topsoil 2:1. The second variable was eco-enzyme concentration at three levels: 0%, 10%, and 20%. These combinations resulted in 12 different treatments, each replicated three times, with two seedlings per replication, requiring a total of 72 polybags (2 seedlings x 3 replications x 12 treatments). Data were analyzed using ANOVA at a 5% significance level, and if significant differences were found, further testing was conducted using DMRT at the same significance level. The findings revealed no significant interaction between the use of rice husk charcoal and eco-enzyme concentrations on the growth of oil palm seedlings. The various ratios of rice husk charcoal (control, 1:4, 1:2, 2:1) had similar effects on seedling growth, and the different eco-enzyme concentrations (0%, 10%, 20%) also showed uniformly positive effects on seedling development.